Relationship Between Estrogen and Idiopathic Mandibular Condylar Resorption: A Systematic Literature Review - Palesik, Benedikta; Musulas, Tomas; Vasiliauskas, Arūnas; Razukevičius, Dainius; Lopatienė, Kristina (Medicina (Kaunas, Lithuania), 2025)
Background and Objectives: Pain in the TMJ is the second most common in the orofacial region. The objective of this systematic review was to assess whether a decrease in estrogen levels increases the risk of idiopathic condylar resorption by reviewing relevant literature and evidence. Material and Methods: This systematic review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. A comprehensive search was performed in the PubMed (Medline), Science Direct (Elsevier), and Web of Science electronic databases. Results: The initial database search identified a total number of 453 studies. After applying the selection criteria, 36 articles were selected for a full-text analysis, and nine studies involving 1105 patients were included in the systematic review. According to the Newcastle–Ottawa Scale (NOS), two of the included articles were graded as being of “Moderate” quality and one was of “Fair” quality. After evaluating the rest of the articles according to the AXIS tool for cross-sectional studies, we generally found that the reliability is moderate. The results show that the decrease in estrogen promotes the occurrence of inflammation in the temporomandibular joint, and some sources mention that it increases the occurrence of idiopathic joint resorption, but we did not establish a complete correlation between the level of estrogen and idiopathic joint resorption. Conclusions: This systematic review indicates that there is no evidence suggesting that fluctuations in estrogen levels contribute to idiopathic mandibular condylar resorption, but reduced estrogen levels can be associated with chronic pain in the temporomandibular joint.